1998
DOI: 10.1007/s004170050098
|View full text |Cite
|
Sign up to set email alerts
|

Retinal capillary density in patients with arterial hypertension: 2-year follow-up

Abstract: The continuous decrease of capillary flow velocity demonstrates a progression of altered microcirculation in patients with essential hypertension whose blood pressure was believed to be well controlled. Further studies with this technique may be useful to determine the influence of antihypertensive therapy and may help to identify patients at risk for cerebrovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
2
10
0
1
Order By: Relevance
“…18 In this study, a further reduction of capillary density and capillary blood velocity was observed in the more severe stages of hypertensive retinopathy. This data, revealing progressive microvascular damage, is supported by several clinical and experimental studies showing progressive capillary closure accompanied by an increased resistance and resulting decrease of perfusion in hypertensive humans [21][22][23] and various animal models. [24][25][26][27] In animal models, capillary closure was found to be reversible within the first few weeks, but became irreversible due to structural changes of the vessel wall in the course of time, thus resulting in a permanently increased flow resistance.…”
Section: Discussionsupporting
confidence: 64%
“…18 In this study, a further reduction of capillary density and capillary blood velocity was observed in the more severe stages of hypertensive retinopathy. This data, revealing progressive microvascular damage, is supported by several clinical and experimental studies showing progressive capillary closure accompanied by an increased resistance and resulting decrease of perfusion in hypertensive humans [21][22][23] and various animal models. [24][25][26][27] In animal models, capillary closure was found to be reversible within the first few weeks, but became irreversible due to structural changes of the vessel wall in the course of time, thus resulting in a permanently increased flow resistance.…”
Section: Discussionsupporting
confidence: 64%
“…Hypertension, for example, has been associated with an increase in the retinal arteriolar length-to-diameter ratio (99,100), increased retinal venular tortuosity (99), reduced branching angle at arteriole bifurcations (101), and reduced microvascular density (99,101,102).…”
Section: Changes In Retinal Vascular Architecture -mentioning
confidence: 99%
“…34 Decreasing perifoveal capillary flow velocity is seen in patients with essential hypertension despite adequate blood pressure control. 35 Measurements of bifurcation angles and retinal arteriolar diameters in response to acute hyperoxic and hypercapneic stress have demonstrated diminished vascular reactivity in hypertensive subjects. 36 Hypertension may be associated with a disadvantageous branching geometry in the retinal vasculature, with reduced circulatory efficiency and microvascular rarefaction.…”
Section: Pathophysiologymentioning
confidence: 99%